1989
DOI: 10.1056/nejm198903303201304
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Thyroid Nodules after Surgical Removal in Patients Irradiated in Childhood for Benign Conditions

Abstract: To determine the incidence of benign thyroid nodules and the risk factors for their recurrence after surgical removal, we followed 511 patients for 1 to 40.6 years (median, 11.2) after surgery for benign thyroid nodules arising after local irradiation for unrelated benign diseases in childhood. Recurrent thyroid nodules developed in 100 patients (19.5 percent). The risk of recurrence correlated inversely with the amount of thyroid tissue removed. Women had a higher recurrence rate than men (28.4 percent vs. 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(24 citation statements)
references
References 15 publications
2
20
1
1
Order By: Relevance
“…However, resolution of focal lesions was seen only in the patients on thyroxine. Fogelfeld et al (1989), in a study of 511 patients who had surgery for benign thyroid nodules arising after radiotherapy to the neck for benign disease in childhood, demonstrated that treatment with thyroxine reduced the number of recurrences of benign nodules but did not affect the rate of thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, resolution of focal lesions was seen only in the patients on thyroxine. Fogelfeld et al (1989), in a study of 511 patients who had surgery for benign thyroid nodules arising after radiotherapy to the neck for benign disease in childhood, demonstrated that treatment with thyroxine reduced the number of recurrences of benign nodules but did not affect the rate of thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown by Fogelfeld et al (1989) that recurrence of thyroid nodules after surgical removal in patients irradiated in childhood for benign conditions is related to the amount of thyroid tissue remaining. In view of these findings and the continuing risk of malignant change in a previously irradiated thyroid gland, unilateral lobectomy in a patient with multiple focal abnormalities of the thyroid on ultrasound is of doubtful benefit as the patient will need to be on thyroxine and will also need to continue to have regular thyroid ultrasound scans.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormone has also been used in pediatric patients with radiation-induced thyroid nodules in which the formation of subsequent nodules has been shown to be reduced (148,149). It is not clear if this data can be extrapolated to pediatric patients with spontaneous nodules, and LT 4 therapy had no effect on the incidence of thyroid cancer (148).…”
Section: Recommendation Rating: E [B6] How Should Thyroid Nodules Be mentioning
confidence: 99%
“…29 More recently, around the time the utility of suppression therapy began to be called into question, Fogelfeld reported that irradiated patients treated with suppression therapy after subtotal thyroidectomy developed fewer benign (not malignant) thyroid nodules than those who were not treated with thyroid hormone. 30 …”
Section: Basis and Originsmentioning
confidence: 99%